A Comparative analysis of conditional clauses in english and persian: text analysis - Mohammad Abdollahi-Guilani; Mohamad Subakir Mohd Yasin; Tan, Kim Hua (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This article compares the application of conditional clauses in English and Persian. Based on two classical literary works, East of Eden by John Steinbeck (1952) and Missing Solooch (In Persian Ja-ye Khali-ye Solooch) by Mahmood Dolatabadi (1979), conditional clauses were retrieved and analysed. The findings indicated that Persian and English have some similarities and differences in terms of the type of conditionals and conjunctions. English seems to employ more conditionals than Persian does. Among the different types of conditionals, type one shows to be more frequent in both languages, while Persian type 2 is mostly representative of type 3 concept. Persian appears to freely employ the subject-fronting strategy to place emphasis on the subject by assigning the subject to an initial position before ‘if’. In both languages, the if-clause is mainly initial in imperative and declarative statements. Reverse conditionals and the deletion of ‘if’ in certain types suggesting high formality do not exist in Persian. Unlike English, Persian does not combine ‘if’ with adjectives and past participles and hence contracted conditionals and the courtesy-bearing structure of English are not common in Persian conditionals. Compared to Persian, the high frequency of English conditionals is also supported by the corpus of Hamshari, an Iranian newspaper, the Time Magazine corpus and Corpus of Contemporary American English.